1999
DOI: 10.1002/(sici)1099-1166(199912)14:12<1006::aid-gps47>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

The Cambridge cognitive examination (CAMCOG): validation of the Hebrew version in elderly demented patients

Abstract: Background and purpose The CAMCOG is the second most popular cognitive testing instrument in use by Israeli clinicians. The present study examines the reliability and validity of a Hebrew version of the CAMCOG in a group of dementia sufferers in a clinical setting. Method Study participants included 36 dementia sufferers and 19 control non‐demented, depressed elderly subjects, consecutive referrals to an outpatient psychogeriatric service and an ‘open’ ward of a psychiatric hospital. Operational clinical crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 27 publications
2
16
1
Order By: Relevance
“…Study participants with AD and MCI were identified in Germany through the memory clinics of the Department of General Psychiatry, Heidelberg University, Heidelberg (Germany) and the Central Institute of Mental Health, Mannheim (Germany), respectively, and in Israel through the psychogeriatric center of the Tel Aviv Sourasky Medical Center. A comprehensive medical, neuropsychological, and neuropsychiatric assessment, including the Consortium to Establish a Registry for Alzheimer’s Disease (CERAD) standardized procedure for the evaluation and diagnosis of patients with cognitive impairments (Morris, Heyman, Mohs, & Hughes, 1989; German version by Thalmann et al, 2000) in Germany and the CAMCOG-R (Hebrew version by Heinik, Werner, Mendel, Raikher, & Bleich, 1999; Roth, Huppert, Tym, & Mountjoy, 1998) in Israel, was carried out.…”
Section: Methodsmentioning
confidence: 99%
“…Study participants with AD and MCI were identified in Germany through the memory clinics of the Department of General Psychiatry, Heidelberg University, Heidelberg (Germany) and the Central Institute of Mental Health, Mannheim (Germany), respectively, and in Israel through the psychogeriatric center of the Tel Aviv Sourasky Medical Center. A comprehensive medical, neuropsychological, and neuropsychiatric assessment, including the Consortium to Establish a Registry for Alzheimer’s Disease (CERAD) standardized procedure for the evaluation and diagnosis of patients with cognitive impairments (Morris, Heyman, Mohs, & Hughes, 1989; German version by Thalmann et al, 2000) in Germany and the CAMCOG-R (Hebrew version by Heinik, Werner, Mendel, Raikher, & Bleich, 1999; Roth, Huppert, Tym, & Mountjoy, 1998) in Israel, was carried out.…”
Section: Methodsmentioning
confidence: 99%
“…Fasting blood samples were obtained from all participants early in the morning via the antecubital vein, and an automatic biochemical analyzer (Swedish Modular DPP AYL-5-001) was used to determine the levels of the following biochemical indices: serum ALP, Alanine Aminotransferase (ALT), Aspartate Aminotransferase (AST), creatinine, Blood Urea Nitrogen (BUN), Fasting Blood Glucose (FBG), triglyceride, total cholesterol, High-Density Lipoprotein Cholesterol (HDL-C), and Low-Density Lipoprotein Cholesterol (LDL-C). The Minimental State Examination (MMSE) and the Cambridge Cognitive Examination-Chinese version (CAMCOG-C) were administered to evaluate neuropsychological status [14,15]; the CAMCOG-C includes scales assessing orientation, language (expression and understanding), memory (remote, recent, learning), attention, praxis, calculation, abstract thinking, and perception.…”
Section: Data Collectionmentioning
confidence: 99%
“…The operational difficulties during the interrater reliability study, which demanded the presence of two raters in the interview room at the same time, caused the studied sample to be smaller than that of the test-retest. However, it does not seem to us that this fact jeopardized the quality of the results, since similar studies were made with samples containing 40 to 55 subjects 8,10 .…”
Section: Test-retest Reliabilitymentioning
confidence: 99%
“…The complexity of the instrument demands training for the raters and the copyright is reserved by the Cambridge University Press. several reliability and validity studies analysing the first version of the instrument (CAMCOG) have been published 3,[8][9][10] , the same being true of the revised version (CAMCOG-R) [11][12][13][14][15] .In Brazil, the only study found by the authors which validates instruments from this country's perspective was the one written by Bottino et al 16 , who made a translation and an adaptation into Portuguese of CAMdEX, and studied the reliability of this Brazilian version using 40 elderly subjects. The interrater reliability, which was evaluated using the ICC, proved to be high, varying from 0.79 to 0.99 for a pair of psychiatrists who applied the instrument, and from 0.67 to 1.0 for another pair (p<0.001).…”
mentioning
confidence: 99%